THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE TO OBEY HEALTH PROTOCOL IN SCHOOL AGE CHILDREN: HUBUNGAN PENGETAHUAN DAN SIKAP MENAATI PROTOKOL KESEHATAN PADA ANAK USIA SEKOLAH - Laurensius Aditya Yoga Pratama; Linda Sari Barus; Ferdinan Sihombing (Jurnal Kesehatan, 2022)
This research is motivated by the establishment of face-to-face learning in schools and children are at risk of contracting COVID-19 if they do not comply with health protocols. This study aims to determine the relationship between knowledge and attitudes to obeying health protocols in school-age children. This study uses a quantitative method with a correlation design with a cross-sectional approach. Data collection was carried out by distributing questionnaire to 105 students at the Cianjur private elementary school. Respondents fill out knowledge and attitude questionnaire. Bivariate data analysis using chi-square test. The results showed that more than half of the respondents were male (55.2%), 11 years old (29.5%), 5th-grade elementary school (28.6%), had good knowledge (77.1%), and positive attitude towards health protocols (54.3%). The results of the chi-square test showed that there was a relationship between knowledge and attitude towards obeying health protocols in school-age children (p-value = 0.013). The results of the study found that there were still those who had sufficient and less knowledge, and respondents who had good knowledge still had negative attitudes. Researchers suggest for school-age children to use this research as information in order to increase awareness that health protocols are important to prevent the transmission of COVID19, and for teachers to use more effective media in providing education on health protocols to increase knowledge that affects attitude formation.